Monetary policy and durable goods - Robert B. Barsky; Christoph E. Boehm; Christopher L. House; Miles S. Kimball (Federal Reserve Bank of Chicago, 2016)
We analyze monetary policy in a New Keynesian model with durable and non-durable goods each with a separate degree of price rigidity. The model behavior is governed by two New Keynesian Phillips Curves. If durable goods are sufficiently long-lived we obtain an intriguing variant of the well-known "divine coincidence." In our model, the output gap depends only on inflation in the durable goods sector. We then analyze the optimal Taylor rule for this economy. If the monetary authority wants to stabilize the aggregate output gap, it places much more emphasis on stabilizing durable goods inflation (relative to its share of value-added in the economy). In contrast, if the monetary authority values stabilizing aggregate inflation, then it is optimal to respond to sectoral inflation in direct proportion to their shares of economic activity. Our results flow from the inherently high interest elasticity of demand for durable goods. We use numerical methods to verify the robustness of our analytical results for a broader class of model parameterizations.
Keywords: E31; E32; E52; 330; Taylor rule; inflation targeting; economic stabilization